Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fphar.2018.01138
|View full text |Cite
|
Sign up to set email alerts
|

Sweroside Alleviated Aconitine-Induced Cardiac Toxicity in H9c2 Cardiomyoblast Cell Line

Abstract: Aconitine is the main bioactive ingredient of Aconitum plants, which are well-known botanical herbs in China. Aconitine is also notorious for its high cardiotoxicity, as it can induce life-threatening ventricular arrhythmias. Unfortunately, there are few effective antidotes to aconitine toxicity. This study aimed to evaluate the potent protective effects of the ingredients from V. baillonii on aconitine toxicity on H9c2 cell line. Cell viability was assessed by methylthiazoltetrazolium bromide (MTT). Intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Cell viability was measured by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) (M2128, Sigma Chemical Co. St. Louis, MO, USA) assay, as previously described. 28 Briefly, cells were cultured in 96-well plates at a density of 1×10 4…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Cell viability was measured by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) (M2128, Sigma Chemical Co. St. Louis, MO, USA) assay, as previously described. 28 Briefly, cells were cultured in 96-well plates at a density of 1×10 4…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…However, samples from Sichuan province showed a higher content of swertiamarin, and pharmacological research has revealed that this characteristic compound possesses anti-diabetic and anti-hyperlipidemic effects [28], and inhibits liver fibrosis [29]. Additionally, samples from Qinghai province have shown a higher content of sweroside, which exhibited a hepatoprotective effect [30], protective effects on osteoporosis [31], and aconitine-induced cardiac toxicity effects [32]. In view of the above reasons, it remains a challenge to estimate the herb quality of different populations.…”
Section: Discussionmentioning
confidence: 99%
“…The other is drug combination. Aconite herbal medicines are frequently formulated with Ginseng, 13,72,73 Glycyrrhiza, 74 and Sweroside, 75,76 Paeoniflorin, 77‐79 Ganjiang, 80‐82 and so forth. Ginsenoside Rg1, the main active ingredient of Ginseng, can alter the pharmacokinetic behavior of AC and accelerate the metabolism of the toxic alkaloid to less toxic monoester alkaloids in the liver 83 .…”
Section: Introductionmentioning
confidence: 99%